Energy abundance, trade and specialisation - Michielsen, Thomas; Gerlagh, Reyer; Mathys, Nicole (My University, 2015)
Do countries with large energy endowments have larger energy-intensive sectors? We answer this question empirically using a panel with 14 high-income countries from Europe, America and Asia and 10 broad sectors, from 1970 to 1997. Energy-abundant countries have 7 to 10 percent higher employment and 13 to 17 percent higher net exports per value added in energy-intensive sectors vis-a`-vis otherwise comparable countries. Conversely, energy-scarce countries specialize in non-energy-intensive sectors.